TRPS1 Confers Multidrug Resistance of Breast Cancer Cells by Regulating BCRP Expression - Hu, Jing; Zhang, Hui; Liu, Long; Han, Bo; Zhou, Gengyin; Su, Peng (Frontiers in Oncology, 2020)
Multidrug resistance (MDR) is the major obstruction in the successful treatment of breast cancer (BCa). The elucidation of molecular events that confer chemoresistance of BCa is of major therapeutic importance. Several studies have elucidated the correlation of TRPS1 and BCa. Here we focused on the role of TRPS1 in acquisition of chemoresistance, and reported a unique role of TRPS1 renders BCa cells resistant to chemotherapeutic drugs via the regulation of BCRP expression. Bioinformation analysis based on publicly available BCa data suggested that TRPS1 overexpression linked to chemoresistance. Mechanistically, TRPS1 regulated BCRP expression and efflux transportation. Overexpression of TRPS1 led to upregulation of BCRP while its inhibition resulted in repression of BCRP. The correlation of TRPS1 and BCRP was further confirmed by immunohistochemistry in 180 BCa samples. MTT assay demonstrated that manipulation of TRPS1 expression affects the chemosensitivity of BCa cells. In total, high expression of TRPS1 confers MDR of BCa which is mediated by BCRP. Our data demonstrated a new insight into mechanisms and strategies to overcome chemoresistance in BCa.